DROUGHT-RESISTANT SOYBEAN VARIETIES FOR STEPPE AND FOREST-STEPPE OF UKRAINE - Biliavska, L. H.; Biliavskyi, Yu. V.; Diyanova, A. A.; Mirny, N. V. (Scientific Progress & Innovations, 2021)
The article presents the results of analyzing the current state of soybean production. The best companies producing soybean seeds in Ukraine have been identified “Soievyi Vik” scientific seed breeding company, the National Scientific Centre the “Institute of Arable Farming of the National Academy of Agrarian Sciences”, Plant Breeding and Genetics Institute – the National Centre for Seed Breeding and Cultivar Studying of the National Academy of Agrarian Sciences, and Poltava State Agrarian Academy have a high rating among the national scientific breeding institutions. Indicators of soybean yield in all regions of Ukraine have been given. In connection with global climate change, it is necessary to test varieties of different ecological and geographical origin in production conditions, to determine their peculiarities, economically valuable features that characterize compliance with specific climatic zones of Ukraine. It has been established that climatic characteristics of Poltava region, which is located in the Forest-Steppe of Ukraine, have become more arid according to the analysis of many-year meteorological observations. The dynamics of indicators of soybean gross harvest in Poltava region for the period of 2002–2020 has been analyzed taking into account the amount of precipitation during the growing season. In the modern conditions of market transformations and innovation processes in the agro-industrial complex, the problems concerning further strategy of developing and increasing the effectiveness of the national system of soybean production in Ukraine has remained unsolved. The number of certified farms for soybean seed production in Ukraine is decreasing. The following soybean varieties have been created in the research laboratory of Breeding, seed production and varietal agro-technology of soybean at Poltava State Agrarian University: Almaz, Antratsyt, Adamos, Aleksandryt, Akvamaryn and Avantiuryn. These varieties are included in the State Register of Plant Varieties Suitable for Spreading in Ukraine. Indicators of agricultural suitability of these varieties and their advantages have been presented. Varieties of Poltava selection are drought-resistant, resistant to diseases and pests, do not lodge, and beans do not crack at seed maturing. The peculiarities of the varieties are rapid moisture transmission at the time of seed maturation, high protein and oil content. These varieties are guaranteed preceding crops for winter crops in the Steppe and Forest-Steppe of Ukraine. According to the results of production testing on “Hryha” farm in Poltava district of Poltava region, it has been established that the varieties of Poltava State Agrarian Academy compete well with new varieties of foreign selection.